2012
DOI: 10.1148/radiol.11110106
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Tumors: Region-of-Interest versus Volumetric Analysis for Quantification of Attenuation at CT

Abstract: Measurements of hepatic tumor attenuation at multidetector CT are reproducible. An approach based on the evaluation of whole-lesion attenuation demonstrated better reproducibility than ROI measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 34 publications
3
18
1
Order By: Relevance
“…Previous studies indicate advantages of whole tumor volume coverage for target lesion analysis, leading to an improvement in reproducibility and a reduction of selection bias [43]. Furthermore, it has been shown that volumetric analysis of CT perfusion values reflects tumor heterogeneity more accurately than measurements in 2D ROIs [12].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate advantages of whole tumor volume coverage for target lesion analysis, leading to an improvement in reproducibility and a reduction of selection bias [43]. Furthermore, it has been shown that volumetric analysis of CT perfusion values reflects tumor heterogeneity more accurately than measurements in 2D ROIs [12].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study, designed in response to that limitation, demonstrated that evaluation of the attenuation of the entire volume of a liver lesion (three-dimensional measurement) has less variability and better reproducibility than the two-dimensional ROI measurement (25).…”
Section: Modified Ct Response Evaluation Criteria (Choi Criteria)mentioning
confidence: 99%
“…Second, volumetric functional MR imaging criteria that can be used to assess viable tumor tissue and provide a strong predictor of response and survival. Software developments have enabled easy, reliable, and reproducible volumetric evaluation of liver lesions (15,17,32). We used proprietary software based on these techniques to analyze two well-described biomarkers of tumor had a 2-year survival rate of 83%, whereas patients classified as single-parameter responders and those classified as nonresponders had 2-year survival rates of 43% and 14%, respectively.…”
Section: Gastrointestinal Imaging: Unresectable Hepatocellular Carcinmentioning
confidence: 99%